Evaluasi Pelaksanaan Webinar Pusdiklat Perdagangan Dengan Menggunakan Text Mining: Analisis Saran Peserta Webinar - Lukitowati, Hari Linda; Paryatno, Luksi (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2021)
The Trade Education and Training Center (Pusdiklat Perdagangan) participates in the development of competencies and skills of the Indonesian people. One of contribution is organizing webinars through the learning management system (LMS) Kudagang. As an education and training center that organizes infographic webinars, Pusdiklat Perdagangan hopes to provide the best service. Therefore, evaluation is a mandatory thing that must be done. The infographic became a webinar topic that was given to participants, both academics and professionals. To provide optimal service, Pusdiklat Perdagangan evaluates webinar activities through participant suggestions. The purpose of this study is to identify things that need to be addressed and improved in the implementation of future webinars so that the quality of services provided is optimal and identify topics and webinar materials that are really needed by the community. Suggestions from participants in the form of text are processed and analyzed using text mining. The data analysis consisted of two parts: (1) analysis of suggestions regarding the webinar activities; (2) suggestions for the next webinar topic. The results of the analysis of participant suggestions indicate several things that need to be improved in the implementation of the webinar, including the audio quality, the practice duration, the technique in delivering material, and the role of the host in guiding the webinar activities. The webinar topic suggestions given by the participants to Pusdiklat Perdagangan are advanced infographics, social media management, public speaking, effective communication, and how to write scientific articles